2014
DOI: 10.3390/app4030390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two-Photon Stark Shift on the Multi-Frequency Raman Spectra

Abstract: High order Raman generation has received considerable attention as a possible method for generating ultrashort pulses. A large number of Raman orders can be generated when the Raman-active medium is pumped by two laser pulses that have a frequency separation equal to the Raman transition frequency. High order Raman generation has been studied in the different temporal regimes, namely: adiabatic, where the pump pulses are much longer than the coherence time of the transition; transient, where the pulse duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The shifted shoulder is consistently longer in duration than the Raman pulse and, except for the timed case, is higher in amplitude than the Raman pulse. The higher amplitude of the red-shifted pulse with a time delay of 333 fs is consistent with the observations in our earlier work [10], which showed that the amplitude of the red-shifted peak grew with increasing anti-Stokes order until there was only the shoulder at the highest orders for this time delay between pump pulses. We expect that this is due to the pump pulse instantaneous frequency separation being on resonance with the dressed states for this delay time.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The shifted shoulder is consistently longer in duration than the Raman pulse and, except for the timed case, is higher in amplitude than the Raman pulse. The higher amplitude of the red-shifted pulse with a time delay of 333 fs is consistent with the observations in our earlier work [10], which showed that the amplitude of the red-shifted peak grew with increasing anti-Stokes order until there was only the shoulder at the highest orders for this time delay between pump pulses. We expect that this is due to the pump pulse instantaneous frequency separation being on resonance with the dressed states for this delay time.…”
Section: Discussionsupporting
confidence: 91%
“…We have investigated these red-shifted spectra under different instantaneous frequency separations and input energies. The results showed that the red-shifted spectrum is not a result of four-wave mixing but could be the result of a two-photon dressed-state Rabi frequency shift [10].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The anti-Stokes lines, which lie in the normal dispersion region over most of the fiber length, appear to be slightly red-shifted relative to their expected wavelengths, especially for the higher order lines (a similar effect was observed in [17], where it was ascribed to a Stark shift of the Raman levels).…”
supporting
confidence: 52%
“…Katsuragawa's group reported the carrier envelope offset control of octave-spanning Raman comb by using dual-frequency laser radiation locked on a single laser cavity and, simultaneously, its second harmonic [11]. Broadband spectra based on multifrequency Raman generation were also studied in photonic crystal fiber [12] and hollow fibers filled with SF6 [13]. Meanwhile, the molecular modulation method has been extended to the continuous-wave (CW) domain.…”
Section: Introductionmentioning
confidence: 99%